Anatomy of Pelvic leak points in the context of varicose veins - Delfrate, Roberto (Phlebologie, 2021)
Pelvic venous networks (competent themselves or not) can be the origin of reflux in the superficial leg veins. They are frequently involved in recurrences after classical venous treatment options, as they are not treated in that context. Studies based on various assessments (clinical, ultrasound, venography) conclude that around 10 % of women with varicose vein have their origin in pelvic leaks points, this incidence is 4 times higher in multiparous than in nulliparous. Claude Franceschi first analyzed and described the reflux pathways for this pelvic leak points. The most frequently involved escape points or “Pelvic Leak Points” are the perineal points (PP), draining through the labial region to the leg and the inguinal points through the inguinal ring (IP). Others are the Clitoridian point (CP), gluteal points (GP) and obturatorian point (OP). Their investigation has to be performed in standing position and using Valsalva – but the most important part of the investigation is the anatomic knowledge about the different pathways.
Keywords: parietal pelvic leak points PLPs; varicose veins of pelvic origin